Fabrication of Liquid Crystal Cell with Corrugated and Parallel Electrodes. Issue 1 (June 2014) - Yang, Ya‐Ting; Chang, Wei‐Fu; Chen, Po‐Jen; Chiu, Tien‐Lung; Lin, Chi‐Feng; Lee, Jiunn‐Yih; Liu, Kou‐Chen; Lee, Jiun‐Haw
Abstract We fabricated a liquid crystal (LC) cell with electrodes on both substrates which are periodically corrugated and parallel to each other. It creates an electric field oblique to substrate direction. Polymer dispersed LC fabricated in such a cell showed higher contrast ratio and wider viewing angle performance than a conventional planar one.